2021
DOI: 10.3389/fped.2021.679572
|View full text |Cite
|
Sign up to set email alerts
|

sVEGFR1 Is Enriched in Hepatic Vein Blood—Evidence for a Provisional Hepatic Factor Candidate?

Abstract: Background: Pulmonary arteriovenous malformations (PAVMs) are common sequelae of palliated univentricular congenital heart disease, yet their pathogenesis remain poorly defined. In this preliminary study, we used paired patient blood samples to identify potential hepatic factor candidates enriched in hepatic vein blood.Methods: Paired venous blood samples were collected from the hepatic vein (HV) and superior vena cava (SVC) from children 0 to 10 years with univentricular and biventricular congenital heart dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…It remains unknown if these findings reflect a different stage of PAVM pathogenesis or are unrelated to in vivo physiology. Subsequently, we also observed multiple differences in circulating protein levels between the SVC and HV, including proteins involved in vascular angiogenic pathways and inflammatory pathways [43]. In this study, our group proposed soluble vascular endothelial growth factor receptor 1 (sVEGFR1) as a potential hepatic factor candidate.…”
Section: Emerging Datamentioning
confidence: 94%
See 1 more Smart Citation
“…It remains unknown if these findings reflect a different stage of PAVM pathogenesis or are unrelated to in vivo physiology. Subsequently, we also observed multiple differences in circulating protein levels between the SVC and HV, including proteins involved in vascular angiogenic pathways and inflammatory pathways [43]. In this study, our group proposed soluble vascular endothelial growth factor receptor 1 (sVEGFR1) as a potential hepatic factor candidate.…”
Section: Emerging Datamentioning
confidence: 94%
“…In addition to the study by Capasso et al, several recent studies collected paired blood samples from the SVC (lacking hepatic factor) and IVC/HV (rich in hepatic factor) in attempts to characterize the differences between SVC and HV blood [42][43][44]. Using serum from a heterogenous group of patients composed of biventricular and single ventricle CHD, we incubated primary human pulmonary microvascular ECs with patient serum samples.…”
Section: Emerging Datamentioning
confidence: 99%
“…Several groups recently started analyzing paired blood samples from the hepatic vein and SVC under the premise that hepatic factor is enriched in hepatic vein blood ( 9 13 ). In one of the first publications using this approach, Capasso et al investigated whether BMP9 and BMP10 were potential hepatic factor candidates ( 10 ).…”
Section: More Recent Hepatic Factor Studies Using Paired Patient Bloo...mentioning
confidence: 99%
“…Last, we recently identified that soluble vascular endothelial growth factor receptor 1 (sVEGFR1, also known as sFLT1) was significantly enriched in hepatic vein serum compared to SVC serum from a heterogenous cohort of children with CHD ( 13 ). Because increased VEGF signaling is associated with AVMs and supplemental sVEGFR1 can inhibit brain AVMs ( 14 17 ), we speculated that sVEGFR1 may be a potential hepatic factor candidate.…”
Section: More Recent Hepatic Factor Studies Using Paired Patient Bloo...mentioning
confidence: 99%
“…Although the lack of hepatic venous effluent directly perfusing the pulmonary arteries and the loss of pulsatile pulmonary blood flow have been identified as major etiological factors contributing to the development of PAVMs, their pathogenetic mechanism still remains unclear ( 1 ). Spearman et al ( 2 ) suggested that soluble vascular endothelial growth factor receptor 1 (sVEGFR1) could be a potential hepatic factor candidate involved in the pathogenesis of PAVMs after surgical palliation for patients with univentricular heart.…”
Section: Introductionmentioning
confidence: 99%